Acetylcholine From Tuft Cells: The Updated Insights Beyond Its Immune and Chemosensory Functions - Pan, Jun; Zhang, Leyi; Shao, Xuan; Huang, Jian (Frontiers in Cell and Developmental Biology, 2020)
Tuft cells, rare solitary chemosensory cells, are distributed in mucosal epithelium throughout mammalian organs. Their nomenclatures are various in different organs and may be confused with other similar cells. Current studies mainly focus on their chemosensory ability and immune functions in type 2 inflammation. Several state-of-the-art reviews have already systematically discussed their role in immune responses. However, given that tuft cells are one of the crucial components of non-neuronal cholinergic system, the functions of tuft cell derived acetylcholine (ACh) and the underlying mechanisms remain intricated. Existing evidence demonstrated that tuft cell derived ACh participates in maintaining epithelial homeostasis, modulating airway remodeling, regulating reflexes, promoting muscle constriction, inducing neurogenic inflammation, initiating carcinogenesis and producing ATP. In this review, the ACh biosynthesis pathways and potential clinical applications of tuft cells have been proposed. More importantly, the main pathophysiological roles and the underlying mechanisms of tuft cell derived ACh are summarized and discussed.